PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT TALANG KELAPA KABUPATEN BANYUASIN - Rohmial Rohmial (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2020)
The work environment is anything that exists around the worker and a physical or nonphysical working condition that can affect employees in completing their tasks or work, and can affect the employees' good or bad performance. This study aims to determine the effect of physical and non-physical work environment on employee performance in the Talang Kelapa Sub-District Office, Banyuasin District.The research method used was a quantitative method using primary and secondary data sources, with data analysis techniques using the classic assumptions namely normality test, multicollinearity test, heteroscedasticity test, linearity test with multiple linear regression analysis and hypothesis testing namely simultaneous test (f test) partial (t test) and coefficient of determination test (R2). In this study used a sample of 36 employees of the State Civil Apparatus (ASN) at the Talang Kelapa Sub-District Office Banyuasin.The results of this study indicate if the physical work environment has a significant effect on employee performance and is positively related, this can be seen from the t value of 3.169 while the t value of the distribution table 0.05 (5%) of 2.034 then t count> t table (3.169 > 2,034) and a significance value of 0.03 <0.05 different from the results of the t test in a non-physical work environment that does not have an influence on employee performance. It can be seen that the t value is 2.022, while the t table distribution value is 0.05 (5%) of 2.034, then the t value is <t table (2.022 <2.034) and the significance value is 0.06> 0.05. The influence of the physical work environment and non-physical work environment on employee performance has an influence together (10,910> 3.28) with Sig f 0.00 <0.05. Then the simultaneous test (F) physical work environment and non-physical work environment have an influence together on employee performance. Keywords: Physical Work Environment, Non-Physical Work Environment, Performance